What Defines the Perfect Wine Tourism Experience? Evidence from a Best–Worst Approach - Caterina Fucile Franceschini; Elisa Giampietri; Eugenio Pomarici (Agriculture)
This paper investigates wine tourists’ preferences for the attributes of the wine tourism experience (WTEXP) in Italy and Turkey, exploring cross-cultural differences and similarities in two countries with diverse wine tourism development. Data were collected through an online survey of 253 wine consumers, and the Best–Worst Scaling method was employed in both countries to assess the perceived importance of selected WTEXP attributes that influence tourists’ choices. The samples were then segmented using cluster analysis based on key attitudinal scales (e.g., wine involvement), with BWS applied to each segment to further examine visitor preferences. The results show that both Italian and Turkish wine tourists prioritized expert-led tours but differed in other preferences. Italian tourists valued the winery’s aesthetic appeal, while Turkish tourists favored pre-visit informative sessions. Additionally, Italians placed less importance on accompanying events, while Turks considered the reputation of the wine, winery, or wine region the least significant factor. These preferences also varied within the clusters identified in each sample. This research represents the first comparison of consumer preferences in wine tourism between Turkey, a developing market, and Italy, a traditional Old World wine producer, while considering the diversity within each group. The findings provide key insights for wine tourism stakeholders, such as wineries and tourism managers, offering actionable recommendations to tailor their offerings for specific tourist segments to attract a larger number of wine tourists, enhance their experience, and foster sustainable growth of wine tourism.